Method for evaluating purity of high-purity quartz sand based on quartz raw material indexes

CN122983183APending Publication Date: 2026-10-27HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610813616.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,该方法需检测的元素种类繁多,检测成本较高、数据处理较为复杂、效率低,且最终仅能提供原料中各杂质元素的含量信息,仍无法直接反映经提纯后产物的实际二氧化硅含量,使得评价结果与生产实际之间往往存在一定偏差

Benefits of technology

[0017]本发明提供一种基于石英原料指标评估高纯石英砂纯度的方法,至少具有如下有益效果:本发明提供一种基于石英原料指标评估高纯石英砂纯度的方法,通过构建石英原料特征参数与提纯后产物纯度之间的定量评估模型,仅需测试石英原料中的铝含量、钛含量及水分含量,即可快速、准确地评估提纯后石英的纯度,具体而言,铝和钛是石英中最具代表性且最难去除的杂质元素,两者在常规提纯工艺中均表现出极强的不可迁移性,即原料中的初始含量与提纯后产物中的残余含量之间具有高度的定量传递关系,直接决定了提纯后产物的纯度上限,同时,石英原料中的水分含量在高温煅烧过程中影响颗粒的微裂纹发育和杂质暴露程度,是影响提纯效率的关键工艺因素,本发明以铝含量、钛含量作为原料本征品质的核心指标,以水含量作为工艺适配性的调控指标,构建了多指标联合的评估模型,实现了对石英原料提纯潜力的科学、量化表征。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122983183A_ABST
    Figure CN122983183A_ABST
Patent Text Reader

Abstract

The application provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indexes, comprising the following steps: obtaining the mass percentage a of aluminum elements in the quartz raw material, with the unit being ppm; obtaining the mass percentage b of titanium elements in the quartz raw material, with the unit being ppm; obtaining the mass percentage content c of water in the quartz raw material; performing purification treatment on the quartz raw material to obtain a quartz product; and calculating the purity S of the quartz product according to Formula 1: Formula 1, wherein β0 is 0.99999189, β1 is -7.88*10-4, β2 is -5.96*10-3, and β3 is -4.532*10-2. ‑7 ‑7 ‑4 The method for evaluating the purity of high-purity quartz sand based on quartz raw material indexes can efficiently and accurately predict the purification quality of quartz at the raw material stage.​​
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mineral analysis and testing technology, specifically to a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators. Background Technology

[0002] High-purity quartz is an indispensable key material for high-tech industries such as semiconductors, photovoltaics, and optical communications. Its purity and quality stability directly affect the performance and yield of downstream high-end products. With the rapid development of these strategic emerging industries, the market demand for high-purity quartz continues to grow, and the quality requirements for it are becoming increasingly stringent.

[0003] In the production of high-purity quartz, the quality evaluation of raw materials is a crucial step in determining the quality of the final product. Currently, most industry methods for evaluating the quality of quartz raw materials still rely on actually purifying the raw materials before analyzing and testing the products. While this "purify first, evaluate later" approach can obtain relatively accurate product indicators, the process involves multiple steps such as crushing, grinding, sorting, and chemical treatment, resulting in a cumbersome evaluation process, long testing cycles, and high overall costs.

[0004] To address the aforementioned issues, existing technologies employ direct elemental analysis of quartz raw materials. These methods typically utilize inductively coupled plasma mass spectrometry (ICP-MS) and X-ray fluorescence spectroscopy (XRF) to comprehensively and quantitatively detect various impurity elements such as aluminum, iron, titanium, calcium, sodium, and potassium in the raw materials. The quality grade of the raw materials is indirectly assessed based on the content of each element. However, this method requires the detection of numerous elements, resulting in high testing costs, complex data processing, and low efficiency. Furthermore, it only provides information on the content of each impurity element in the raw material and cannot directly reflect the actual silica content of the purified product, often leading to a discrepancy between the evaluation results and actual production practices.

[0005] Therefore, how to achieve efficient and accurate prediction of quartz purification quality at the raw material stage has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] This invention provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators. It is applicable to the evaluation of the purity of purified quartz and can achieve efficient and accurate prediction of the purity of purified products at the raw material stage.

[0007] This invention provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators, comprising the following steps: obtaining the mass percentage 'a' of aluminum in the quartz raw material (in ppm); obtaining the mass percentage 'b' of titanium in the quartz raw material (in ppm); obtaining the mass percentage 'c' of water in the quartz raw material; purifying the quartz raw material to obtain high-purity quartz sand; and calculating the purity S of the high-purity quartz sand according to Formula 1. Formula 1, where β0 is 0.99999189 and β1 is -7.88 × 10⁻⁶. -7 β2 is -5.96 × 10 -7 β3 is -4.532 × 10 -4 .

[0008] Optionally, the mass percentage of aluminum (a) and the mass percentage of titanium (b) in the quartz raw material are obtained by laser ablation inductively coupled plasma mass spectrometry.

[0009] Optionally, the test parameters for laser ablation inductively coupled plasma mass spectrometry are as follows: the laser beam diameter is 30 μm to 50 μm; standard samples are tested sequentially after every 10 sample points to correct instrument drift; the gas background acquisition time for each analysis point is 20 s to 30 s, and the signal acquisition time is 35 s to 45 s; the standard samples include NIST610, NIST612, and NIST614.

[0010] Optionally, the mass percentage c of water in the quartz raw material can be obtained by Fourier transform infrared spectroscopy.

[0011] Optionally, the test conditions for the Fourier transform infrared spectroscopy are: wavenumber range of 2000 cm⁻¹ to 4000 cm⁻¹. -1 The method employs unpolarized light with a beam size of 20μm×20μm to 40μm×40μm; and / or, it further includes: preparing the quartz raw material into a double-sided polished sheet with a thickness of 150μm to 250μm before testing by the Fourier transform infrared spectroscopy, immersing the sheet in acetone for 24 hours or more, cleaning it, and then drying it at 90℃ to 110℃ for 12 hours or more.

[0012] Optionally, the purification process includes, in sequence, calcination, water quenching, crushing and screening, magnetic separation, flotation, and acid washing.

[0013] Optionally, the calcination process includes: calcining the quartz raw material at 950℃~1000℃ for 2h~3h; the water quenching process includes: quenching the calcined quartz raw material in water at 20℃~25℃; the crushing and screening process includes: subjecting the water-quenched quartz raw material to a first-stage crushing and a second-stage crushing in sequence, and then screening the crushed quartz raw material using a standard sieve of 0.1mm~0.3mm; wherein the equipment for the first-stage crushing includes a hammer crusher, and the equipment for the second-stage crushing includes a double-roll crusher.

[0014] Optionally, the magnetic separation process includes: mixing the crushed and screened quartz raw material with a first solvent to obtain a material system with a quartz raw material mass percentage of 20%~30%; subjecting the material system to a first magnetic separation and a second magnetic separation in sequence; after the magnetic separation treatment is completed, a non-magnetic material containing quartz raw material is obtained; filtering and drying the non-magnetic material containing quartz raw material to obtain quartz fine sand; the magnetic field strength of the first magnetic separation is 0.5T~1.0T, and the magnetic field strength of the second magnetic separation is 1.5T~2.0T; the first solvent includes water.

[0015] Optionally, the flotation process includes: mixing a raw material system comprising the quartz concentrate, a second solvent, an acid modifier, a collector, and a frother, followed by aeration, foam removal, filtration, and drying to obtain flotation concentrate; the second solvent comprises water; the acid modifier comprises hydrogen fluoride; the collector comprises at least one of dodecylamine and sodium petroleum sulfonate; and the frother comprises at least one of pine oil and methyl isobutyl methanol.

[0016] Optionally, the acid washing process includes: subjecting the raw material system comprising the flotation concentrate and acid solution to a water bath at 80°C to 100°C for 2 to 6 hours, and obtaining the high-purity quartz sand after washing, filtration, and drying; the acid solution comprises acid and water, the acid comprising at least one of hydrochloric acid and hydrofluoric acid, and the mass ratio of the acid solution to the flotation concentrate is (2 to 5): 1.

[0017] This invention provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators, which has at least the following beneficial effects: This invention provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators. By constructing a quantitative evaluation model between the characteristic parameters of quartz raw materials and the purity of the purified product, it is only necessary to test the aluminum content, titanium content, and moisture content in the quartz raw materials to quickly and accurately evaluate the purity of the purified quartz. Specifically, aluminum and titanium are the most representative and most difficult-to-remove impurity elements in quartz. Both exhibit strong non-migratory properties in conventional purification processes, meaning that there is a high degree of quantitative transfer relationship between the initial content in the raw materials and the residual content in the purified product, directly determining the upper limit of the purity of the purified product. At the same time, the moisture content in the quartz raw materials affects the development of microcracks in the particles and the degree of impurity exposure during high-temperature calcination, which is a key process factor affecting purification efficiency. This invention uses aluminum content and titanium content as the core indicators of the intrinsic quality of the raw materials and water content as the control indicator of process adaptability, constructing a multi-indicator joint evaluation model to achieve a scientific and quantitative characterization of the purification potential of quartz raw materials. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 A flowchart of a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators provided by the present invention;

[0020] Figure 2 A linear relationship diagram between the aluminum content in quartz raw materials and the aluminum content in high-purity quartz sand in the construction of the model of Formula 1 of this invention;

[0021] Figure 3 A linear relationship diagram between the titanium content in Formula 1 of this invention and the titanium content in high-purity quartz sand is shown.

[0022] Figure 4 A linear relationship diagram between the water content in the quartz raw material and the water content in the high-purity quartz sand in the construction of the model of Formula 1 of this invention;

[0023] Figure 5 This is a scatter plot of the true and predicted values ​​of the training set in the model construction of Equation 1 of this invention.

[0024] Figure 6 This is a scatter plot of the true values ​​and predicted values ​​of the validation set in the model construction of Equation 1 of this invention. Detailed Implementation

[0025] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below. The specific embodiments listed below are merely descriptions of the principles and features of the present invention, and the examples are only for explaining the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] This invention provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators, comprising the following steps: obtaining the mass percentage 'a' of aluminum in the quartz raw material (in ppm); obtaining the mass percentage 'b' of titanium in the quartz raw material (in ppm); obtaining the mass percentage 'c' of water in the quartz raw material; purifying the quartz raw material to obtain high-purity quartz sand; and calculating the purity S of the high-purity quartz sand according to Formula 1. Formula 1, where β0 is 0.99999189 and β1 is -7.88 × 10⁻⁶. -7 β2 is -5.96 × 10 -7 β3 is -4.532 × 10 -4 .

[0027] Based on research and analysis, this invention provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators. By constructing a quantitative evaluation model between the characteristic parameters of quartz raw materials and the purity of the purified product, the purity of the purified quartz can be quickly and accurately evaluated simply by testing the aluminum, titanium, and moisture content in the quartz raw materials. Specifically, aluminum and titanium are the most representative and difficult-to-remove impurity elements in quartz. Both exhibit strong non-migratory properties in conventional purification processes, meaning there is a high degree of quantitative transfer between the initial content in the raw materials and the residual content in the purified product, directly determining the upper limit of the purity of the purified product. At the same time, the moisture content in the quartz raw materials affects the development of microcracks and the degree of impurity exposure during high-temperature calcination, and is a key process factor affecting purification efficiency. This invention uses aluminum and titanium content as core indicators of the intrinsic quality of the raw materials and water content as a control indicator for process adaptability, constructing a multi-indicator joint evaluation model to achieve a scientific and quantitative characterization of the purification potential of quartz raw materials.

[0028] In this embodiment of the invention, the quartz raw material includes aluminum (Al), titanium (Ti), and water.

[0029] Furthermore, the quartz raw material may also include at least one of the following elements: iron (Fe), calcium (Ca), potassium (K), sodium (Na), lithium (Li), manganese (Mn), magnesium (Mg), nickel (Ni), copper (Cu), chromium (Cr), and barium (Ba).

[0030] In-situ trace element analysis revealed that among the various trace impurity elements contained in the quartz raw material, only the contents of aluminum and titanium showed a stable and significant positive correlation with their corresponding contents in the purified high-purity quartz sand (e.g., ...). Figure 2 , Figure 3 As shown, the goodness of fit R before and after aluminum purification treatment is... 2 The concentration of Al and Ti in the raw material is as high as 0.9107, indicating that the Al and Ti content in the raw material can directly and effectively predict the Al and Ti content in the purified high-purity quartz sand. However, the content of other common impurity elements (such as iron, potassium, and sodium) does not exhibit this pattern before and after purification and cannot be used for reliable prediction. Therefore, by detecting the Al and Ti content in the raw material, the impurity level of the purified product can be accurately predicted. Furthermore, there is a significant negative correlation between the water content in the quartz raw material and the silica (SiO2) purity of the purified high-purity quartz sand (e.g., ...). Figure 4 As shown in the figure, the lower the water content of the raw material, the higher the purity of the high-purity quartz sand (SiO2) obtained after purification.

[0031] The specific formula for calculating the purity of high-purity quartz sand is as follows:

[0032] Equation 2.

[0033] This formula was obtained by analyzing and training the data on the purity, element content, and water content of multiple sets of quartz raw materials and the purity, element content, and water content of high-purity quartz sand, as well as the results of their correlation analysis, using a partial least squares regression algorithm.

[0034] In some embodiments, the mass percentage of aluminum (a) and the mass percentage of titanium (b) in the quartz raw material are obtained by laser ablation inductively coupled plasma mass spectrometry.

[0035] In existing technologies, the distribution of impurity elements in quartz raw materials is often extremely uneven. Some impurities exist in the form of fine inclusions inside the quartz lattice. Simple elemental analysis is difficult to effectively distinguish whether the impurities exist in the quartz crystal or originate from the associated mineral phase. The impact paths and removal difficulties of these two types of impurities on subsequent purification processes are fundamentally different. If they are not distinguished, it is easy to lead to distorted evaluation results.

[0036] To address the aforementioned issues, this invention employs laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) for in-situ micro-area analysis of aluminum and titanium content in quartz raw materials. This method enables selective ablation of the intrinsic regions of the quartz crystal, effectively avoiding interference from associated mineral phases and fluid inclusions, thereby accurately obtaining the aluminum and titanium content within the quartz lattice. In this way, this invention overcomes the limitation of traditional elemental analysis in distinguishing the state of impurities, ensuring that the detection results truly reflect the intrinsic quality of the quartz raw material and providing a reliable data foundation for accurate assessment of subsequent purification potential.

[0037] Furthermore, the test parameters for laser ablation inductively coupled plasma mass spectrometry are as follows: the laser beam diameter can be 30μm~50μm, and standard samples are tested sequentially after every 10 sample points to correct instrument drift. The gas background acquisition time for each analysis point can be 20s~30s, and the signal acquisition time can be 35s~45s.

[0038] For example, the testing process of laser ablation inductively coupled plasma mass spectrometry may specifically include: carbonizing the quartz raw material sample, then testing it under a laser beam spot with a diameter of 30μm~50μm, testing 10 sample points and then testing 3 standard samples (NIST610, NIST612, NIST614) in sequence, the gas background acquisition time for each analysis point can be 20s~30s, the signal acquisition time can be 35s~45s, and then the data is analyzed and processed.

[0039] The synergistic limitation of the test parameter range of the aforementioned laser ablation inductively coupled plasma mass spectrometry method can effectively suppress instrument drift, reduce background noise, and achieve precise in-situ ablation of micro-areas. This significantly improves the accuracy and stability of the determination of trace elements such as aluminum and titanium in quartz raw materials, providing a reliable data basis for subsequent product purity assessment. At the same time, this testing technology is mature, fast, and has clear standards, making it suitable for rapid evaluation at mine sites or quality inspection of incoming materials in factories.

[0040] The laser beam diameter can be 30μm to 50μm, for example, 30, 40, 50μm or any combination thereof, preferably 40μm.

[0041] The laser beam diameter meets the above range and is much smaller than the quartz particle size, enabling targeted ablation of the intrinsic region of the quartz crystal. This effectively avoids interference areas such as associated mineral phases, fluid inclusions, and cracks, ensuring that the measured aluminum and titanium content truly reflects the impurity level inside the quartz lattice, thus balancing spatial resolution and detection sensitivity.

[0042] If the standard sample points meet the above range, the drift correction interval can be controlled within a reasonable range, avoiding both excessive frequency leading to decreased testing efficiency and excessively long intervals leading to correction failure.

[0043] The gas background sampling time can be 20s to 30s, for example, 20, 25, 30s or any combination of two of them, preferably 25s.

[0044] If the gas background acquisition time meets the above range, it can better acquire the background signal in the carrier gas (usually helium or argon) before the laser is turned on, thereby effectively deducting the instrument's background noise and the interference of trace impurity elements in the carrier gas.

[0045] The signal acquisition time can be 35s to 45s, for example, 35, 40, 45s or any combination of two of them, preferably 40s.

[0046] If the signal acquisition time meets the above range, it can ensure the stable plateau period of the covered signal, obtain enough data points for integration processing, and reduce the impact of single-point noise on the results.

[0047] Standard samples can use the Standard Reference Materials (SRM) from the National Institute of Standards and Technology (NIST), specifically NIST 610, NIST 612, and NIST 614.

[0048] In some specific implementations, the mass percentage c of water in the quartz raw material can be obtained by Fourier transform infrared spectroscopy.

[0049] This invention employs Fourier transform infrared spectroscopy to determine the water content in quartz raw materials, offering comprehensive advantages such as in-situ micro-area analysis, differentiation between water and structural water, non-destructive testing, high sensitivity, and fast testing speed. This method can accurately obtain the intrinsic water content of quartz crystals, effectively eliminating interference from associated minerals and structural water, and overcoming the shortcomings of traditional moisture detection methods, such as inability to distinguish water types, susceptibility to interference, and sample damage.

[0050] Specifically, the test conditions for Fourier transform infrared spectroscopy are: wavenumber range of 2000 cm⁻¹. -1 ~4000cm -1 Unpolarized light is used, with beam size ranging from 20μm×20μm to 40μm×40μm.

[0051] The test conditions of Fourier transform infrared spectroscopy meet the above range. The wavenumber range can completely cover the characteristic peaks of water and avoid interference from the quartz matrix. The beam size can realize in-situ analysis of micro-areas and eliminate interference from associated minerals. The synergistic effect of the two ensures the accuracy, representativeness and low content detection sensitivity of the determination of water content in quartz raw materials.

[0052] The wavenumber range is 2000 cm⁻¹ -1 ~4000cm -1 For example, 2000, 2500, 3000, 3500, 4000 cm -1 Or a range consisting of any two of them.

[0053] The beam size can be from 20μm×20μm to 40μm×40μm, for example, 20μm×20μm, 30μm×30μm, 40μm×40μm or any combination thereof, preferably 30μm×30μm.

[0054] Furthermore, the background is scanned after each sample analysis to subtract the background noise. The number of scans for both the sample and background can be 256 to 512, and the resolution can be set to 4 cm. -1 ~16cm -1 .

[0055] Before testing by Fourier transform infrared spectroscopy, the quartz raw material was prepared into double-sided polished thin sheets with a thickness of 150μm~250μm, and the thin sheets were immersed in acetone for 24 hours or more, cleaned, and dried at 90℃~110℃ for 12 hours or more.

[0056] For example, the above process may specifically include: preparing quartz raw material into a double-sided polished sheet with a thickness of 150μm~250μm, immersing the sheet in acetone for 24 hours or more, cleaning it with anhydrous ethanol, and drying it at 90℃~110℃ for 12 hours or more.

[0057] The thickness of the quartz raw material can be a double-sided polished sheet of 150μm to 250μm, such as 150, 200, 250μm or any combination thereof, thereby ensuring that infrared light passes directly through the sample in transmission mode, minimizing light loss and obtaining a spectrum with a high signal-to-noise ratio.

[0058] Immersing the thin sheet in acetone for 24 hours or more, such as 24, 25, 26, 27, 28, 29, 30 hours or any combination thereof, allows the quartz raw material sample (rock sample) to be separated from the glass plate (which serves as a temporary support substrate for carrying the sample during processing). This dissolves the hot melt adhesive on the sample surface (which acts as a temporary adhesive to fix the quartz raw material sample onto the glass plate; the hot melt adhesive is liquid when heated and solidifies upon cooling, providing sufficient adhesion to resist the mechanical forces during polishing).

[0059] The drying temperature can be 90℃~110℃, for example, 90, 100, 110℃ or any combination thereof; the drying time can be 12h or more, for example, 12, 13, 14, 15h or any combination thereof. Drying under the above conditions can more thoroughly remove water from the surface and cracks of the quartz raw material sample.

[0060] High-purity quartz sand is obtained by purifying (refining) quartz raw materials. The purification process includes calcination, water quenching, crushing and screening, magnetic separation, flotation, and acid washing.

[0061] After the above purification process, the purity of high-purity quartz sand can be evaluated using Formula 1.

[0062] Specifically, the calcination process includes calcining the quartz raw material at 950℃~1000℃ for 2h~3h.

[0063] For example, the specific process of calcination treatment may include: calcining the quartz raw material in a muffle furnace, the calcination temperature may be 950℃~1000℃, and the calcination time may be 2h~3h.

[0064] The calcination temperature can be 950℃~1000℃, for example, 950, 960, 970, 980, 990, 1000℃ or any combination thereof, preferably 980℃.

[0065] The calcination temperature meets the above range, which effectively promotes the transformation of quartz crystal form, allows the gas-liquid inclusions to fully burst and expose internal impurities, and avoids excessive sintering of particles, thus creating favorable conditions for subsequent water quenching and pickling.

[0066] The calcination time can be 2h to 3h, for example, 2, 2.5, 3h or any combination thereof, preferably 2h.

[0067] The calcination time meets the above range, which effectively promotes the transformation of quartz crystal form, allows the gas-liquid inclusions to fully burst and expose internal impurities, and avoids excessive sintering of particles, thus creating favorable conditions for subsequent water quenching and pickling.

[0068] The water quenching process includes quenching the calcined quartz raw material in water at 20℃~25℃.

[0069] For example, the water quenching process may specifically include: immediately after calcination, the calcined quartz raw material is water quenched in cold water at 20°C to 25°C.

[0070] Water quenching can utilize temperature differences to generate intense thermal stress in the calcined high-temperature quartz raw material, causing a large number of microcracks to form inside the quartz particles, thereby increasing the specific surface area and exposing impurities in the inclusions, significantly improving the reaction efficiency of impurities with acid in the subsequent pickling process.

[0071] The temperature of the cold water can be 20℃~25℃, for example, 20, 21, 22, 23, 24, 25 or any combination thereof.

[0072] When the water temperature meets the above range, the temperature difference can be used to generate severe thermal stress in the calcined high-temperature quartz raw material, causing a large number of microcracks to form inside the quartz particles, thereby increasing the specific surface area and exposing impurities in the inclusions, significantly improving the reaction efficiency of impurities and acid in the subsequent pickling process.

[0073] The crushing and screening process includes: the water-quenched quartz raw material undergoes a first-stage crushing and a second-stage crushing in sequence, and the crushed quartz raw material is screened using a standard sieve of 0.1mm~0.3mm.

[0074] For example, the crushing and screening process may specifically include: subjecting the water-quenched quartz raw material to a first stage of crushing and a second stage of crushing in sequence, and the crushed quartz raw material may be screened multiple times using a standard sieve of 0.1mm to 0.3mm.

[0075] Crushing and screening can fully dissociate quartz raw materials from associated impurity minerals along the interface, exposing the impurity particles encased inside the quartz. This provides effective conditions for impurity removal in subsequent processes such as magnetic separation, flotation, and acid washing, avoiding low purification efficiency due to insufficient dissociation.

[0076] The equipment used in the crushing process may include zirconia. The equipment used in the first stage of crushing may include a hammer crusher, and the equipment used in the second stage of crushing may include a double roll crusher. Specifically, the crushing equipment used in the first stage of crushing may include a zirconia hammer crusher, and the crushing equipment used in the second stage of crushing may include a zirconia double roll crusher.

[0077] The aperture of the standard sieve can be 0.1mm to 0.3mm, such as 0.1, 0.2, 0.3mm or any combination thereof. The crushed quartz raw material can be screened multiple times using standard sieves with different apertures. For example, 0.3mm and 0.1mm standard sieves can be used sequentially for grading to obtain quartz raw material samples of the target particle size.

[0078] The magnetic separation process includes: mixing the sieved quartz raw material with a first solvent to prepare a material system with a quartz raw material mass percentage of 20%~30%, and subjecting the material system to a first magnetic separation and a second magnetic separation in sequence. After the magnetic separation treatment is completed, the non-magnetic material containing the quartz raw material is filtered and dried to obtain quartz fine sand.

[0079] For example, the magnetic separation process may specifically include: mixing the sieved quartz raw material with a first solvent to prepare a material system with a quartz raw material mass percentage of 20%~30% (quartz raw material accounts for 20%~30% of the total mass of quartz raw material and the first solvent), and subjecting the material system to a first magnetic separation and a second magnetic separation in a periodic pulsating high gradient magnetic separator in sequence. After the magnetic separation process is completed, the non-magnetic material including the quartz raw material is filtered and dried to obtain quartz fine sand.

[0080] Magnetic separation can effectively remove magnetic and weakly magnetic impurities such as magnetite, hematite, and biotite, significantly reducing iron content. When combined with processes such as calcination, flotation, and acid washing, it can achieve tiered removal of impurities and improve overall purification efficiency.

[0081] The mass percentage of quartz raw materials can be 20% to 30%, for example, 20%, 25%, 30% or any combination thereof.

[0082] The quartz raw material's mass percentage content meets the above range, which enables the material system to maintain a suitable flow state and ensures that the quartz particles pass smoothly through the magnetic field area during the magnetic separation process; at the same time, it can avoid problems such as reduced single-pass throughput and decreased efficiency caused by excessively low slurry concentration, thus balancing the magnetic separation effect and production processing efficiency.

[0083] Specifically, multiple material systems can be configured (e.g., 3 material systems, each with a mass of 150g of quartz raw material), and these systems can be added sequentially and evenly to a periodic pulsating high gradient magnetic separator for magnetic separation.

[0084] By controlling the amount of material fed at one time and maintaining an appropriate material layer thickness, the mechanical entrainment and loss of non-magnetic particles caused by excessively thick material layers in the magnetic separator are avoided, thereby improving the separation accuracy of the magnetic separation process and the yield of quartz fine sand.

[0085] The two-stage magnetic separation can adopt a medium-magnetic-strong magnetic field method. Specifically, the magnetic field strength of the first magnetic separation can be 0.5T~1.0T (medium magnetic field), such as 0.5, 0.6, 0.7, 0.8, 0.9, 1.0T or any combination thereof; the magnetic field strength of the second magnetic separation can be 1.5T~2.0T (strong magnetic field), such as 1.5, 1.6, 1.7, 1.8, 1.9, 2.0T or any combination thereof.

[0086] The first solvent may include water (such as deionized water).

[0087] The flotation process may include: mixing a raw material system comprising quartz concentrate, a second solvent, an acid modifier, a collector, and a frother, followed by aeration, foam removal, filtration, and drying to obtain flotation concentrate.

[0088] For example, the flotation process may specifically include: mixing quartz concentrate with a second solvent to prepare a slurry with a quartz concentrate mass percentage of 30% to 40%, adjusting the pH of the slurry to 2 to 3 using an acid regulator, then adding a collector, the amount of which can be 350 g / t to 450 g / t, stirring and mixing evenly, then adding a frother, the amount of which can be 40 g / t to 50 g / t, stirring evenly, then aerating and skimming the bubbles, and finally filtering and drying to obtain flotation concentrate.

[0089] Flotation can efficiently remove associated silicate impurities such as feldspar and mica. These impurities have similar density and chemical properties to quartz, making them difficult to separate effectively by gravity separation or magnetic separation. Flotation, on the other hand, utilizes the differences in the wettability of mineral surfaces and achieves selective separation by carrying them with air bubbles. Moreover, the process does not cause mechanical damage to quartz crystals and forms a good synergistic effect with magnetic separation and acid washing.

[0090] The second solvent may include water.

[0091] The concentration of the slurry can be 30% to 40%, for example, 30%, 35%, 40% or any combination thereof, preferably 35%.

[0092] Acidity regulators may include hydrogen fluoride.

[0093] The pH of the slurry can be 2 to 3, for example, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3 or any combination thereof. By adjusting the pH value to control the surface charge of the minerals, the collector can selectively adsorb onto the target impurities rather than the quartz surface, which is beneficial for the removal of impurities and improves the purity of high-purity quartz sand.

[0094] Collectors include at least one of dodecylamine and sodium petroleum sulfonate.

[0095] Collectors that meet the above criteria have polar groups that can adsorb onto the surface of feldspar and mica, and non-polar hydrophobic chains that face the solution, causing impurity minerals to change from hydrophilic to hydrophobic, which is beneficial for the removal of impurities.

[0096] The amount of collector added can be 350 g / t to 450 g / t, for example, 350, 400, 450 g / t or any combination thereof, preferably 400 g / t.

[0097] When the amount of collector added is within the above range, it can effectively cover the surface of quartz sand particles under acidic conditions (pH=2~3), thereby achieving efficient collection of impurities such as feldspar and mica.

[0098] The foaming agent may include at least one of pine oil and methyl isobutyl alcohol (MIBC).

[0099] The foaming agent meets the above requirements, can reduce the gas-liquid interfacial tension, generate a large number of stable and fine bubbles, increase the chance of bubbles colliding and adhering with hydrophobic impurities, and finally generate an upward bubble flow through aeration, carrying hydrophobic impurities to float to the surface of the slurry, and the foam layer is scraped off in time by the foam scraping device, thus completing the separation of impurities from quartz and improving the purity of high-purity quartz sand.

[0100] The amount of foaming agent added can be 40 g / t to 50 g / t, for example, 40, 45, 50 g / t or any combination thereof, preferably 45 g / t.

[0101] The pickling process may include: subjecting the raw material system, including flotation concentrate and acid solution, to a water bath at 80℃~100℃ for 2h~6h, and then washing, filtering, and drying to obtain high-purity quartz sand.

[0102] For example, the pickling process may specifically include: subjecting a raw material system including flotation concentrate and acid solution to a water bath at 80°C to 100°C for 2 to 6 hours, washing until neutral, filtering, and drying to obtain high-purity quartz sand.

[0103] The acid solution may include both acid and water, and the acid may include at least one of hydrochloric acid (HCl) and hydrofluoric acid (HF).

[0104] Acids, including those mentioned above, can penetrate deep into the microcracks of flotation concentrate, thoroughly dissolving metal oxides and silicate impurities that cannot be reached by magnetic separation and flotation, significantly improving the purity of quartz (SiO2).

[0105] The mass ratio of acid solution to flotation concentrate can be (2~5):1, for example, 2:1, 3:1, 4:1, 5:1 or any combination thereof, preferably 2:1.

[0106] When the mass ratio of acid solution to flotation concentrate meets the above range, the quartz particles can be evenly dispersed in the acid solution, ensuring that the surface of each particle can fully contact the acid solution, thereby improving the purification efficiency and enhancing the purification effect.

[0107] The temperature of the water bath can be 80℃~100℃, for example, 80, 90, 100 or any combination thereof, preferably 80℃; the water bath time can be 2h~6h, for example, 2h, 3h, 4h, 5h, 6h or any combination thereof, preferably 2h.

[0108] When the temperature or time of the water bath meets the above range, impurities can be removed more effectively, thus improving the purity of high-purity quartz sand.

[0109] The flowchart of the above method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators is as follows: Figure 1 As shown.

[0110] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0111] Example 1

[0112] This embodiment provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators and a method for purifying quartz raw materials. The specific steps are as follows:

[0113] The quartz raw material contains 11.21 ppm aluminum, 2.83 ppm titanium, and 0.0184 wt% water. Substituting into formula 1...

[0114] S = 0.99999189 - 7.88 × 10 -7 ×11.21-5.96×10 -7 ×2.83-4.532×10 -4 ×0.0184=0.99997303,

[0115] The purity of SiO2 obtained was 99.997%, and after purification, high-purity 4N5 quartz could be obtained.

[0116] The purification process specifically includes:

[0117] (1) Calcine the quartz raw material at 950℃ for 2 hours. After the calcination treatment, quickly put it into 20℃ water for water quenching treatment. Then, perform the first stage crushing and the second stage crushing in sequence. The crushed quartz raw material is screened using standard sieves of 0.3mm and 0.1mm respectively.

[0118] (2) Mix the sieved quartz raw material with water (first solvent) to prepare a material system with a quartz raw material mass percentage of 20wt%. The material system is subjected to first magnetic separation (0.5T) and second magnetic separation (1.5T) in sequence. After the magnetic separation treatment is completed, the non-magnetic material including the quartz raw material is filtered and dried to obtain quartz fine sand.

[0119] The raw material system, including quartz sand, water (second solvent), hydrogen fluoride (acid regulator), dodecylamine (collector), and pine oil (foaming agent), is mixed, aerated and skimmed, filtered and dried to obtain flotation sand.

[0120] The raw material system, including flotation concentrate and hydrofluoric acid (acid solution, with a mass ratio of acid solution to flotation concentrate of 2:1), is placed in a water bath at 80°C for 2 hours. After washing, filtering and drying, high-purity quartz sand is obtained.

[0121] Example 2

[0122] This embodiment provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators and a method for purifying quartz raw materials. The specific steps are as follows:

[0123] The quartz raw material contains 4.3 ppm of aluminum, 1.43 ppm of titanium, and 0.0051 wt% water. Substituting into formula 1...

[0124] S = 0.99999189 - 7.88 × 10 -7 ×4.3-5.96×10 -7 ×1.43-4.532×10 -4 ×0.0051=0.99998534,

[0125] The purity of SiO2 obtained was 99.998%, and after purification, high-purity 4N8 quartz could be obtained;

[0126] The purification process specifically includes:

[0127] (1) Calcine the quartz raw material at 1000℃ for 3 hours. After the calcination treatment, quickly put it into 25℃ water for water quenching treatment. Then, perform the first stage crushing and the second stage crushing in sequence. The crushed quartz raw material is screened using standard sieves of 0.3mm and 0.1mm respectively.

[0128] (2) Mix the sieved quartz raw material with water (first solvent) to prepare a material system with a quartz raw material mass percentage of 30wt%. The material system is subjected to first magnetic separation (1.0T) and second magnetic separation (2.0T) in sequence. After the magnetic separation treatment is completed, the non-magnetic material including the quartz raw material is filtered and dried to obtain quartz fine sand.

[0129] The raw material system, including quartz sand, water (second solvent), hydrogen fluoride (acid regulator), dodecylamine (collector), and pine oil (foaming agent), is mixed, aerated and skimmed, filtered and dried to obtain flotation sand.

[0130] The raw material system, including flotation concentrate and hydrofluoric acid (acid solution, with a mass ratio of acid solution to flotation concentrate of 5:1), is placed in a water bath at 100°C for 2 hours. After washing, filtering and drying, high-purity quartz sand is obtained.

[0131] Example 3

[0132] This embodiment provides a method for evaluating the purity of high-purity quartz sand based on quartz raw material indicators and a method for purifying quartz raw materials. The specific steps are as follows:

[0133] The quartz raw material contains 8.59 ppm of aluminum, 2.82 ppm of titanium, and 0.0107 wt% water. Substituting into formula 1...

[0134] S = 0.99999189 - 7.88 × 10 -7 ×8.59-5.96×10 -7 ×2.82-4.532×10 -4 ×0.0107=0.99997859,

[0135] The purity of SiO2 obtained was 99.997%, and after purification, high-purity 4N5 quartz could be obtained.

[0136] The purification process specifically includes:

[0137] (1) Calcine the quartz raw material at 980℃ for 2.5h. After the calcination treatment, quickly put it into 25℃ water for water quenching treatment. Then, perform the first stage crushing and the second stage crushing in sequence. The crushed quartz raw material is screened using standard sieves of 0.3mm and 0.1mm respectively.

[0138] (2) Mix the sieved quartz raw material with water (first solvent) to prepare a material system with a quartz raw material mass percentage of 25wt%. The material system is subjected to first magnetic separation (0.8T) and second magnetic separation (1.8T) in sequence. After the magnetic separation treatment is completed, the non-magnetic material containing quartz raw material is filtered and dried to obtain quartz fine sand.

[0139] The raw material system, including quartz sand, water (second solvent), hydrogen fluoride (acid regulator), dodecylamine (collector), and pine oil (foaming agent), is mixed, aerated and skimmed, filtered and dried to obtain flotation sand.

[0140] The raw material system, including flotation concentrate and hydrofluoric acid (acid solution, with a mass ratio of acid solution to flotation concentrate of 3:1), is placed in a water bath at 90°C for 3 hours. After washing, filtering and drying, high-purity quartz sand is obtained.

[0141] Comparative Example 1

[0142] The quartz raw material contains 49.07 ppm aluminum, 5.16 ppm titanium, and 0.009 wt% water. Substituting into formula 1...

[0143] S = 0.99999189 - 7.88 × 10 -7×49.07-5.96×10 -7 ×5.16-4.532×10 -4 ×0.009=0.99994607,

[0144] The purity of SiO2 obtained was 99.994%. After purification, high-purity 4N5 quartz could not be obtained. The purification process was the same as in Example 1.

[0145] Test case

[0146] 1. Construction of Equation 1

[0147] Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) was used to determine the Al and Ti content in the quartz lattice before purification treatment. LA-ICP-MS can avoid the interference of mineral inclusions such as feldspar and mica and accurately obtain the Al and Ti content in the quartz lattice.

[0148] Ti in the crystal lattice is extremely difficult to remove during purification. A high initial Ti content indicates limited purification potential of the ore. Conversely, the Al content in the crystal lattice directly reflects the upper limit of the quality of the purified high-purity quartz sand. Therefore, determining the Al and Ti content within the crystal lattice of quartz raw materials using LA-ICP-MS can effectively assess the purification potential of quartz raw materials.

[0149] Inductively coupled plasma mass spectrometry (ICP-MS) is used to determine the total content of impurity elements such as Al and Ti in purified high-purity quartz sand. This method is a solution-based method that can simultaneously detect lattice elements and the total amount of elements in inclusions. The test results serve as a quality basis for determining whether the product meets the 4N and other specifications, and are used to verify the effectiveness of the purification treatment.

[0150] The testing procedure for inductively coupled plasma mass spectrometry (ICP-MS) is as follows: The sample is accurately weighed in a clean environment, and high-purity hydrofluoric acid (HF) is added. The sample is then thoroughly digested using a hot plate or microwave digestion method. Subsequently, the sample is heated to dryness to remove all hydrofluoric acid. The residue is reconstituted with dilute nitric acid and brought to a final volume. The target element content is then quantitatively analyzed using inductively coupled plasma mass spectrometry in helium collision mode using a standard curve method.

[0151] The results of the trace element content tests on quartz raw materials (before purification) and high-purity quartz sand (after purification) are shown in Table 1. Pearson correlation coefficient analysis was performed based on the data in Table 1, and the data are shown in Table 2.

[0152] Table 1

[0153]

[0154] The higher Al content measured in purified quartz products compared to unpurified quartz raw materials does not necessarily indicate an actual increase in Al concentration during purification. Rather, it's due to the different objects being detected by the two testing methods. LA-ICP-MS analyzes raw materials by using a micro-area, point-to-point method to avoid mineral inclusions, and the measured Al is primarily composed of substituted impurities in the quartz lattice, resulting in relatively low values. However, ICP-MS analysis of purified samples requires complete digestion, measuring the total Al content, including residual aluminum inclusions. If the purification process fails to completely remove aluminum-containing mineral inclusions (such as feldspar and mica), the ICP-MS result may be higher than the LA-ICP-MS value for Al in the raw material lattice, thus creating the appearance of an "increased" Al content after purification.

[0155] Table 2

[0156]

[0157] According to the Pearson correlation coefficient analysis results shown in Table 2, the Al content before and after purification showed a highly significant positive correlation (r=0.927, p<0.001), indicating that samples with high Al content before purification usually still have relatively high Al content after purification. The Ti content before and after purification also showed a significant positive correlation trend (r=0.520, p=0.069), indicating that Ti content was consistent before and after purification. The Na+K+Li content before and after purification showed a negative correlation (r=-0.692, p=0.009), indicating that the correspondence before and after purification was not stable and the direction of change may differ.

[0158] The water content of the quartz raw material was tested by Fourier transform infrared spectroscopy, and the silica content of the quartz raw material and the silica content of the high-purity quartz sand were tested by laser ablation inductively coupled plasma mass spectrometry. The results were converted to mass percentages and are shown in Table 3. Based on the data of water content of quartz raw material and silica content of high-purity quartz sand in Table 3, Pearson correlation coefficient analysis was performed and the data are shown in Table 4.

[0159] Table 3

[0160]

[0161] Table 4

[0162]

[0163] According to the Pearson correlation coefficient analysis in Table 4, the water content of quartz raw materials is negatively correlated with the SiO2 content of the products (r=-0.3), indicating that the higher the water content in the raw materials, the lower the SiO2 content of the products generally becomes.

[0164] Based on the correlation analysis results, a partial least squares regression algorithm was used to construct a SiO2 purity prediction model. Using the Al, Ti, and water contents in the sample as input variables and SiO2 purity as the output variable, a linear regression relationship was established. Let the SiO2 purity be S, the Al content be a, the Ti content be b, and the water content be c, then the model can be expressed as:

[0165] Formula 1,

[0166] Where β0 is a constant term, and β1, β2, and β3 are the regression coefficients corresponding to each variable. Considering the correlation between the input variables, partial least squares regression is used to reduce the dimensionality of the sample data to improve the stability and predictive ability of the model.

[0167] In the model building process, samples B1, B2, B3, B6, B7, B9, B10, B11, B12, and B13 were first used as the training set, and samples B4, B5, and B8 were used as the validation set. The training set was used to build the partial least squares regression model and optimize the principal components, while the validation set was used to evaluate the model's predictive performance. Simultaneously, combining statistical modeling principles and practical application requirements, the root mean square prediction error (RMSEP) was used to evaluate the model's prediction accuracy, and the root mean square error of cross-validation (RMSECV) was used to measure the model's stability and generalization ability. Smaller RMSEP and RMSECV values ​​indicate smaller prediction errors and better robustness. Therefore, considering the model's fitting effect, predictive ability, and actual error control requirements, RMSEP ≤ 0.08% and RMSECV ≤ 0.05% were used as the criteria for judging model performance. By comparing the model's fitting effect and cross-validation results under different principal component conditions (aluminum content, titanium content, and water content), the results are as follows: Figure 5 As shown.

[0168] Based on the optimized training set, the SiO2 purity prediction equation is obtained as follows:

[0169] Equation 2.

[0170] To verify the effectiveness of the established model, a validation set was used to test the model's predictions. The test results are as follows: Figure 6 As shown.

[0171] The validation results show that the root mean square prediction error (RMSEP) between the predicted and actual values ​​is 0.000610%, which meets the requirement of RMSEP ≤ 0.08%. Further cross-validation on the training set yielded a root mean square cross-validation error (RMSECV) of 0.00105%, which also meets the requirement of RMSECV ≤ 0.05%.

[0172] Next, based on the evaluation model and the parameters obtained from the experiment, we will evaluate whether it can become 4N8 (SiO2≥0.99998) and 4N5 (SiO2≥0.99995).

[0173] Furthermore, to quickly determine whether the purity of SiO2 reaches 4N8, substituting SiO2≥0.99998 into Equation 2, we get:

[0174] 0.99999189-7.88×10 -7 a-5.96×10 -7 b-4.532×10 -4 c≥0.99998,

[0175] After simplification, the judgment relation is obtained:

[0176] -7.88×10 -7 a-5.96×10 -7 b-4.532×10 -4 c≥-1.189×10 -5 ,

[0177] Right now:

[0178] 7.88a + 5.96b + 4532c ≤ 118.9 (Equation 3)

[0179] Therefore, in practical applications, the purity of SiO2 can be quickly assessed by substituting the Al content, Ti content, and water content of the quartz raw material sample into the inequality shown in Equation 3. If Equation 3 is satisfied, the purity of SiO2 in the high-purity quartz sand after purification can be assessed as 4N8 (greater than or equal to 99.998%) high-purity quartz sand; otherwise, it is not satisfied.

[0180] The criteria for determining whether quartz sand with a purity of 4N5 can be obtained after purification are the same as those for 4N8 quartz; when the inequality shown in Equation 4 is satisfied, it can be determined that the corresponding purity requirement is met.

[0181] 7.88a+5.96b+4532c≤418.9 Equation 4.

[0182] 2. Validation of the prediction performance of Equation 1

[0183] The contents of Al, Ti and SiO2 in the quartz products in the examples were tested using laser ablation inductively coupled plasma mass spectrometry, and the results are shown in Table 5.

[0184] Table 5

[0185]

[0186] Conclusion Analysis:

[0187] Based on the silica purity obtained from Table 5, it can be seen that Examples 1 and 3 do not satisfy Equation 3 and satisfy Equation 4, respectively, and the calculated quartz purity S cannot reach 4N8, but can reach 4N5; Example 2 satisfies Equation 3, and the calculated quartz purity S can reach 4N8; Comparative Example 1 does not satisfy Equations 3 and 4, and the calculated quartz purity S cannot reach 4N5. The calculation results of the examples are consistent with the purification experiment results. Therefore, by constructing a quantitative evaluation model between the characteristic parameters of quartz raw materials and the purity of the purified product, and testing the aluminum content, titanium content, and moisture content in the quartz raw materials, the purity of the purified quartz can be quickly and accurately evaluated.

[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for evaluating the purity of quartz products based on quartz raw material indicators, characterized in that, Includes the following steps: Obtain the mass percentage 'a' of aluminum in the quartz raw material, expressed in ppm. Obtain the mass percentage b of titanium in the quartz raw material, in ppm. Obtain the mass percentage c of water in the quartz raw material; The quartz raw material is purified to obtain the quartz product; The purity S of the quartz product was calculated according to Formula 1: Official 1, Where β0 is 0.99999189 and β1 is -7.88 × 10⁻⁶. -7 β2 is -5.96 × 10 -7 β3 is -4.532 × 10 -4 .

2. The method for evaluating the purity of quartz products based on quartz raw material indicators according to claim 1, characterized in that, The mass percentage of aluminum (a) and the mass percentage of titanium (b) in the quartz raw material were obtained by laser ablation inductively coupled plasma mass spectrometry.

3. The method for evaluating the purity of quartz products based on quartz raw material indicators according to claim 2, characterized in that, The test parameters for the laser ablation inductively coupled plasma mass spectrometry method are as follows: the laser beam diameter is 30 μm to 50 μm; after testing 10 sample points, standard samples are tested sequentially to correct instrument drift; the gas background acquisition time for each analysis point is 20 s to 30 s, and the signal acquisition time is 35 s to 45 s; the standard samples include NIST610, NIST612, and NIST614.

4. The method for evaluating the purity of quartz products based on quartz raw material indicators according to any one of claims 1-3, characterized in that, The mass percentage c of water in the quartz raw material was obtained by Fourier transform infrared spectroscopy.

5. The method for evaluating the purity of quartz products based on quartz raw material indicators according to claim 4, characterized in that, The test conditions for the Fourier transform infrared spectroscopy method are: wavenumber range of 2000 cm⁻¹. -1 ~4000cm -1 It uses unpolarized light with a beam size ranging from 20μm×20μm to 40μm×40μm; And / or, further comprising: preparing the quartz raw material into a double-sided polished sheet with a thickness of 150μm~250μm before testing by the Fourier transform infrared spectroscopy, immersing the sheet in acetone for 24h or more, cleaning it, and drying it at 90℃~110℃ for 12h or more.

6. The method for evaluating the purity of quartz products based on quartz raw material indicators according to any one of claims 1-5, characterized in that, The purification process includes, in sequence, calcination, water quenching, crushing and screening, magnetic separation, flotation, and acid washing.

7. The method for evaluating the purity of quartz products based on quartz raw material indicators according to claim 6, characterized in that, The calcination process includes calcining the quartz raw material at 950℃~1000℃ for 2h~3h; The water quenching process includes: quenching the calcined quartz raw material in water at 20°C to 25°C. The crushing and screening process includes: sequentially subjecting the water-quenched quartz raw material to a first stage of crushing and a second stage of crushing, and then screening the crushed quartz raw material using a standard sieve of 0.1mm~0.3mm; wherein the equipment for the first stage of crushing includes a hammer crusher, and the equipment for the second stage of crushing includes a double roll crusher.

8. The method for evaluating the purity of quartz products based on quartz raw material indicators according to claim 6 or 7, characterized in that, The magnetic separation process includes: mixing the crushed and screened quartz raw material with a first solvent to obtain a material system with a quartz raw material mass percentage of 20%~30%; subjecting the material system to a first magnetic separation and a second magnetic separation in sequence; after the magnetic separation treatment is completed, a non-magnetic material containing quartz raw material is obtained; filtering and drying the non-magnetic material containing quartz raw material to obtain quartz fine sand; the magnetic field strength of the first magnetic separation is 0.5T~1.0T, and the magnetic field strength of the second magnetic separation is 1.5T~2.0T; the first solvent includes water.

9. The method for evaluating the purity of quartz products based on quartz raw material indicators according to claim 8, characterized in that, The flotation process includes: mixing a raw material system comprising the quartz concentrate, a second solvent, an acid modifier, a collector, and a frother; aerating and skimming the bubbles; filtering and drying to obtain flotation concentrate; the second solvent comprises water; the acid modifier comprises hydrogen fluoride; the collector comprises at least one of dodecylamine and sodium petroleum sulfonate; and the frother comprises at least one of pine oil and methyl isobutyl methanol.

10. The method for evaluating the purity of quartz products based on quartz raw material indicators according to claim 9, characterized in that, The acid washing process includes: subjecting the raw material system, including the flotation concentrate and acid solution, to a water bath at 80°C to 100°C for 2 to 6 hours, and obtaining the quartz product after washing, filtering, and drying; the acid solution includes acid and water, and the acid includes at least one of hydrochloric acid and hydrofluoric acid, and the mass ratio of the acid solution to the flotation concentrate is (2 to 5): 1.